A phase 2 randomized, double-masked, placebo-controlled study of novel nonsystemic kinase inhibitor TOP1630 for the treatment of dry eye disease - Taylor M (Dove Medical Press, 2019)
Mike Taylor,1 George Ousler,2 Gail Torkildsen,3 Claire Walshe,1 Matthew C T Fyfe,1 Adele Rowley,1 Steve Webber,1 John D Sheppard,4 Ajay Duggal1 1TopiVert Pharma Limited, London, UK; 2Ora Inc., Andover, MA, USA; 3Andover Eye Associates, Andover, MA, USA; 4Virginia Eye Consultants, Norfolk, VA, USA Purpose: To evaluate the safety and efficacy of topical TOP1630, a novel nonsystemic kinase inhibitor, in dry eye disease (DED).Patients and methods: A randomized, double-masked, parallel-group trial of 0.1% TOP1630 ophthalmic solution TID or placebo (vehicle without active drug) was conducted in DED subjects (n=61). Key eligibility criteria consistent with enrolling a moderate to severe DED population included >6 months DED history; OSDI© score ≥18; Schirmer’s test score ≤10 and ≥1 mm/5 minutes; tear film break-up time >1 and <7 seconds; and dry eye exacerbation in corneal staining and ocular discomfort in a Controlled Adverse Environment (CAE®). After a -day run-in period with placebo TID, eligible subjects were randomized to TOP1630 or placebo for 28 days. No supplemental artificial tears or rescue medication were allowed. Results: TOP1630 was safe, well-tolerated, and efficacious in treating DED symptoms and signs. No serious adverse events (AEs) or withdrawals due to treatment emergent AEs occurred. Drop comfort scores showed TOP1630 to be comfortable and comparable with placebo. Significant symptom improvements were seen for TOP1630 vs placebo for ocular discomfort (P=0.02 post-CAE), grittiness/foreign body sensation (on four independent assessment scales, each P<0.05), worst DED symptom (diary, P=0.06), and ocular pain (VAS, P=0.03). Sign improvements were seen for total ocular surface (all regions), corneal sum, and conjunctival sum staining with TOP1630 compared with placebo (each P<0.05).Conclusion: TOP1630 had placebo-like tolerability and produced improvements in multiple symptom and sign endpoints in both environmental and challenge settings. The emergent TOP1630 benefit–risk profile for DED treatment is highly favorable and supports further development. Keywords: dry eye, DED, TOP1630, ocular inflammation